Collective Strategy Formulation: An Experimental Research Assessing the Positive Impact of Group Decision Support System on Work Group - Gassemi, Karim (International Review of Management and Marketing, 2019)
Since the formulation of organizational strategy has been recognized as a collective process, several studies have assessed the usefulness of group decision support system “(GDSS)” inside the collective process of strategy formulation. This research evaluates the impact of GDSS on the collective process of strategy formulation. The competing values approach (CVA) model “CVA” was used as a theoretical basis and framework to evaluate the group's interaction and work. The research model includes one independent variable, two controlled variables and eight dependent variables. Eight research hypotheses were defined and empirically tested. Experimental laboratories with predefined procedures were conducted. 60 participants were randomly defined in groups of five peoples. The results indicate that the group supported by a GDSS perceives the best perception of the collective strategy formulation process comparing to groups supported by manual structure and control groups. Keywords: Group Decision Support System, Collective Strategy Formulation Process, Competing Values Approach Model, Adaptive Structuration Theory, Group Interaction Process JEL Classification: O33 DOI: https://doi.org/10.32479/irmm.8522